Obstetric Cholestasis among Pregnant Women Visiting a Tertiary Care Centre - Indra Yadav; Siddhartha Kumar Yadav; Tarun Pradhan; Anika Yadav; Sabita Jyoti; Rozy Yadav (Journal of Nepal Medical Association, 2023)
Introduction: Obstetric cholestasis is one of the most frequent hepatic disorders specific to pregnancy. It occurs commonly during the latter half of pregnancy. The data regarding this issue is rare in our settings. The aim of this study was to find out the prevalence of obstetric cholestasis among pregnant women visiting a tertiary care centre.